2016
DOI: 10.1136/bmjopen-2016-013120
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study investigating the relationship between cholesterol, cardiovascular risk score and the prescribing of statins in UK primary care: study protocol

Abstract: Introduction: Risk scoring is an integral part of the prevention of cardiovascular disease (CVD) and should form the basis for the decision to offer medication to reduce cholesterol (statins). However, there is a suggestion in the literature that many patients are still initiated on statins based on raised cholesterol rather than a raised CVD risk. It is important, therefore, to investigate the role that lipid levels and CVD risks have in the decision to prescribe. This research will establish how cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
2
1
Order By: Relevance
“…This suggests that even though recommended LDL-C treatment thresholds were not strictly adopted, LDL-C levels were indeed taken into account in the treatment decisions. In addition, we found that undertreatment was less common in patients at very high CV risk compared to patients at high CV risk and thereby were able to show that GPs account for the patients CV risk, which contrasted studies reporting that GPs placed too much emphasis on dyslipidemia rather than absolute CV risk [7,16,17]. Interestingly, among patients with very high CV risk in our study, those with established atherosclerotic CV disease (patients in secondary prevention) were more likely to be initiated on a statin than those without established atherosclerotic CV disease (primary prevention, Table 1).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…This suggests that even though recommended LDL-C treatment thresholds were not strictly adopted, LDL-C levels were indeed taken into account in the treatment decisions. In addition, we found that undertreatment was less common in patients at very high CV risk compared to patients at high CV risk and thereby were able to show that GPs account for the patients CV risk, which contrasted studies reporting that GPs placed too much emphasis on dyslipidemia rather than absolute CV risk [7,16,17]. Interestingly, among patients with very high CV risk in our study, those with established atherosclerotic CV disease (patients in secondary prevention) were more likely to be initiated on a statin than those without established atherosclerotic CV disease (primary prevention, Table 1).…”
Section: Discussioncontrasting
confidence: 66%
“…Given the high prevalence of increased CV risk, guideline-concordant statin treatment is of great concern. Both statin undertreatment, i.e., forgoing statin treatment for patients for whom initiation is recommended, and overtreatment, i.e., the initiation of statin treatment in patients for whom it is not recommended, have been reported [ 7 , 8 , 9 ]. Undertreatment is of highest concern, as it signifies missed opportunities to effectively decrease CV mortality.…”
Section: Introductionmentioning
confidence: 99%
“…For missing data a ‘missing’ category was used. The lipid values were extracted, along with any variables that are included in the QRISK2 calculation or could influence statin prescribing (see protocol paper 31 for full list). Biologically implausible values were excluded (including cases where high-density lipoprotein [HDL] cholesterol was greater than total cholesterol [TC]).…”
Section: Methodsmentioning
confidence: 99%